Nursing actions focused on the environment / sustainability aimed at promoting the health of individuals (Research, Society and Development, 2020)
This study aims to reflect on the actions taken by nurses about the environment and sustainability with a view to promoting the health of individuals. This is a theoretical-reflective study based on references worked in the discipline Nursing Work / health in the socioenvironmental context, during the first semester of 2019 of the Doctoral Program in Nursing of the Graduate Program in Nursing at Universidade Federal do Rio Grande and critical reading on the topic. The results were given through two thematic axes: relationship between environment and human health; Nursing actions focused on the environment / sustainability aimed at promoting the health of individuals. It is concluded that when contemplating actions to encourage sustainability in nursing consultations, in promoting health education activities with an environmental purpose of care, it becomes an important tool in the empowerment of the community, since they are no longer supporting and become main actors.